2016
DOI: 10.1002/we.2067
|View full text |Cite
|
Sign up to set email alerts
|

A linearized numerical model of wind-farm flows

Abstract: A fast and reasonably accurate numerical three‐dimensional wake model able to predict the flow behaviour of a wind farm over a flat terrain has been developed. The model is based on the boundary‐layer approximation of the Navier–Stokes equations, linearized around the incoming atmospheric boundary layer, with the assumption that the wind turbines provide a small perturbation to the velocity field. The linearization of the actuator‐disc theory brought additional insights that could be used to understand the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…We do, however, have reason to believe that the wind farms could cause such consistently observed slowdowns. Separate wind tunnel and LES studies have shown such an effect [12][13][14], and the RANS results herein, which absolutely isolate wind farm impact, include upstream slowdowns that are reasonably consistent with average measured ∆U P,R , whether binned by distance upstream or by wind farm. We therefore conclude that the presence of the wind farms is very likely the primary cause behind the significant wind speed reductions observed at the perimeter masts after COD.…”
Section: Wind Farm Csupporting
confidence: 78%
See 1 more Smart Citation
“…We do, however, have reason to believe that the wind farms could cause such consistently observed slowdowns. Separate wind tunnel and LES studies have shown such an effect [12][13][14], and the RANS results herein, which absolutely isolate wind farm impact, include upstream slowdowns that are reasonably consistent with average measured ∆U P,R , whether binned by distance upstream or by wind farm. We therefore conclude that the presence of the wind farms is very likely the primary cause behind the significant wind speed reductions observed at the perimeter masts after COD.…”
Section: Wind Farm Csupporting
confidence: 78%
“…Yet the literature also includes indications of potential shortcomings in the wakes-only approach. In Ebenhoch [12], wind tunnel measurements and corresponding model predictions revealed a wind speed deficit upstream of a 105-turbine wind farm. The deficit was much larger and Consistent with this approach, research on the fluid dynamic interaction between turbines has, until recently, focused almost exclusively on wakes.…”
Section: Introductionmentioning
confidence: 99%
“…As the model was developed to account for both topography and turbines, it enables both features to be combined and some of the limitations of the current industrial assumptions to be assessed. In order to quantify the effect of topography in wind farms, a three-dimensional simulation was done with a wind farm composed of 10 rows in a staggered arrangement (10 turbines followed by 11 turbines, for a total of 105 turbines), replicating the experiments performed in the Gävle wind tunnel and described in [11,19]. The spacing between the rows was S x = 4D, while the spacing between the turbines in the lateral direction was S y = 2.66D, where D = 45 mm is the turbine diameter (the hub height was z hub = 60 mm).…”
Section: Influence Of Topography In Wind Farmsmentioning
confidence: 99%
“…This will lead to a significant error in the estimated velocity near the rotor (although the velocity magnitude might change inside the cylinder volume, something that does not happen in an actuator disc), but it should not significantly affect the far field. Owing to the limited number of points inside the actuator-disc volume (there should be N p = 3 − 4 points inside each volume, depending on the relative position between the grid and the turbine, so that turbines should not introduce sudden impulses), a multiplicative correction factor of 2δ/(N p x) was introduced in equation (2.9) to compensate for the finite number of points inside the cylinder, as discussed in [11]. Figure 4 shows the comparison between the streamwise velocity of the three cases evaluated in a horizontal plane at constant height from the ground, η = z hub /D.…”
Section: Influence Of Topography In Wind Farmsmentioning
confidence: 99%
See 1 more Smart Citation